(untitled) (Research, Society and Development, 2023)
Objective: To evaluate, through scientific literature, the influence of breastfeeding on facial growth and development. Methods: This is an integrative review, where a search was conducted on the following databases: BVS (Virtual Health Library), Pubmed, and SCIELO (Scientific Electronic Library Online). Results: The research revealed that breastfeeding contributes to the development of dentition, facial structure, and the movements of suction, chewing, swallowing, and breathing, providing advantages to achieve proper bite and quality of life in the future, resulting in a dynamic balance between the face and the oral cavity. Final Considerations: Based on the analysis of the studies, it is evident that dentists play a fundamental role in promoting breastfeeding, as they can guide mothers on the importance of breastfeeding and its impact on the proper development of the child, both nutritionally and skeletally, which contributes to the harmonious orofacial growth of the child.